2010
DOI: 10.1152/ajpregu.00425.2009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of hypoxic injury to the murine placenta

Abstract: Tomlinson TM, Garbow JR, Anderson JR, Engelbach JA, Nelson DM, Sadovsky Y. Magnetic resonance imaging of hypoxic injury to the murine placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 55 publications
(58 reference statements)
0
37
0
Order By: Relevance
“…Moreover, there was no upregulation of placental miR-210 in response to moderate maternal hypoxia. Notably, we used a moderate level of hypoxia (O 2 =12%) because, in our previous studies, we found that this degree of hypoxia caused fetal growth restriction by 10-20%, without excessive fetal loss [16]. In addition, we initiated hypoxia at E11.5, as our goal was to assess the effect of hypoxia on the established placenta and avoid exposure to hypoxia earlier in gestation, when the feto-placental unit develops during physiological hypoxia [17-20].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there was no upregulation of placental miR-210 in response to moderate maternal hypoxia. Notably, we used a moderate level of hypoxia (O 2 =12%) because, in our previous studies, we found that this degree of hypoxia caused fetal growth restriction by 10-20%, without excessive fetal loss [16]. In addition, we initiated hypoxia at E11.5, as our goal was to assess the effect of hypoxia on the established placenta and avoid exposure to hypoxia earlier in gestation, when the feto-placental unit develops during physiological hypoxia [17-20].…”
Section: Resultsmentioning
confidence: 99%
“…We also found that Fabp4 -null fetuses were indistinguishable from their wt littermates with respect to weight and morphology (not shown). Because we previously showed that human trophoblastic FABP4 is upregulated in hypoxia in vitro [21], we assessed the impact of hypoxia (O 2 =12%, E12.5–18.5) on fetal growth, using protocols previously described in our lab [30, 31]. Except for the predicted growth restriction by 10–20% of all mouse fetuses exposed to hypoxia [30, 31], there were no differences among littermates representing the different genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Trophoblast cells migrate toward oxygen in the human placental bed ( Jauniaux et al 2001 ). Alternatively, others have used in vivo chronic hypoxia to overwhelm adaptive responses and create placental injury ( Tomlinson et al 2010; Lai et al 2011 ). Thus, oxygen availability can serve as context-dependent instructive or pathological signals affecting placentation.…”
Section: Regulation Of Invasive Trophoblast Differentiationmentioning
confidence: 99%